Effects of Seed Storage Duration and Matriconditioning Materials on Germination and Seedling Characteristics of Maize - Arief, Ramlah; Koes, Fauziah; Komalasari, Oom (AGRIVITA, Journal of Agricultural Science, 2020)
Matriconditioning treatments have been reported to improve seed and seedling qualities of many crops after certain storage periods. The research was conducted to evaluate different matriconditioning substances on seedlings characteristics of seeds that previously stored in different periods. The research was carried out from October 2015 to April 2016 at the Indonesian Cereal Research Institute (ICERI). The experiment was arranged in factorial completely randomized design to facilitate the combination of two factors. The first factor was seed storage period, i.e. 4, 36 and 72 months, while the second factor dealt with matriconditioning subtances, i.e without matriconditioning, sawdust, carbonized rice hull and rice straw. The results showed that matriconditioning treatments improved seed and seedling qualities of the maize seeds derived from different storage periods. Shorter seed storage period produced seedlings with higher percentage of germination, germination rate, seedling dry weight, shoots and roots lenghts and lower EC. Among the tested matriconditioning substances, carbonized rice hull provided more suitable condition to improve seedling qualities in any seed storage period than saw dust and rice straw.